The effect of proton pump inhibitors and clopidogrel combination to the risk of recurrent stroke - Ngatidjan, Endang Mahati Jarir Atthobari (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2015)
Recurrent stroke is very common among stroke survivors. Clopidogrel is one of the drugs used in the prevention of recurrent stroke. Because clopidogrel may cause gastrointestinal bleeding, the use of proton pump inhibitors may elicite the side effect, but unfortunately this combination may interfere the antiplatelete activity of clopidogrel since both are metabolized by the same enzyme, liver CYP2C19. The aim of this study was to know the effect of proton pump inhibitors on the efficacy of clopidogrel in the prevention of recurrent stroke in Bethesda Hospital, Yogyakarta. This study was a case control study. The sample size of treatment case was 392 patients and control case was 784 patients. The case group was patients with recurrent stroke and the control group was the patients who come to outpatient clinics of Department of Neurology. In this study, matching was made for treatment and control groups on sex, age and their index date. The exposure of the combination was investigated in the last 6 months and categorized as current use (<2 month before index date) and recent use (2-6month before index date). Multivariate analysis showed that there was no association between clopidogrel and proton pump inhibitors to the risk of recurrent stroke OR 1.05 (95% CI 0.56-1.785). Omeprazole was the most used, although there was no significantly increased risk OR 0.46 (95% CI 0.56-3.70). The effect of proton pump inhibitors to the efficacy of clopidogrel has not been known yet in this study, because the amount of total sample that used the combination of this drug was too small.Keywords: clopidogrel - proton pump inhibitors - recurrent stroke - interaction